2021
DOI: 10.3390/math9030276
|View full text |Cite
|
Sign up to set email alerts
|

Double Solutions and Stability Analysis of Micropolar Hybrid Nanofluid with Thermal Radiation Impact on Unsteady Stagnation Point Flow

Abstract: The mathematical modeling of unsteady flow of micropolar Cu–Al2O3/water nanofluid driven by a deformable sheet in stagnation region with thermal radiation effect has been explored numerically. To achieve the system of nonlinear ordinary differential equations (ODEs), we have employed some appropriate transformations and solved it numerically using MATLAB software (built-in solver called bvp4c). Influences of relevant parameters on fluid flow and heat transfer characteristic are discussed and presented in graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Further investigation can be conducted to check the possible value of suction parameter, for example, if l = À1, À0.5, 0, 0.5, 1. There are also a few of references with the similar findings where only limited Radiative hybrid nanofluid values of the stretching/shrinking parameter could produce second solution (Anuar and Bachok, 2021;Yashkun et al, 2020). For the stretching case, the heat transfer rate is higher than the shrinking case, but the addition of R reduces the numerical values of for shrinking case.…”
Section: Resultsmentioning
confidence: 71%
“…Further investigation can be conducted to check the possible value of suction parameter, for example, if l = À1, À0.5, 0, 0.5, 1. There are also a few of references with the similar findings where only limited Radiative hybrid nanofluid values of the stretching/shrinking parameter could produce second solution (Anuar and Bachok, 2021;Yashkun et al, 2020). For the stretching case, the heat transfer rate is higher than the shrinking case, but the addition of R reduces the numerical values of for shrinking case.…”
Section: Resultsmentioning
confidence: 71%
“…In some boundary layer flow problems, non-unique solutions have generally been found for linear shrinking sheet cases. For instance, non-unique solutions have been observed by Wang [26], Bachok et al [27], Kamal et al [28] and Anuar and Bachok [29], among others for the stagnation flow problem. Meanwhile, Bhattacharyya and Vajravelu [30], Bachok et al [31] and Anuar et al [32] have observed the occurrence of non-unique solutions in their investigation of stagnation flow when the sheet is shrunk exponentially.…”
Section: Introductionmentioning
confidence: 98%
“…Jamshed et al 31 interpreted the Williamson hybrid nanoliquid flow with an engine oil-based liquid by employing the Cattaneo-Christov heat flux model. Anuar and Bachok 32 highlighted the unsteady micropolar hybrid nanoliquid flow at a stagnation point under the occurrence of thermal radiation. They attained numerical solutions to their problem.…”
Section: Introductionmentioning
confidence: 99%